Yersinia pestis and Yersinia pseudotuberculosis infection: a regulatory RNA perspective - Vadyvaloo, Viveka; Martínez-Chavarría, Luary C. (Frontiers in Microbiology, 2015)
Yersinia pestis, responsible for causing fulminant plague, has evolved clonally from the enteric pathogen, Y. pseudotuberculosis, which in contrast, causes a relatively benign enteric illness. An 97% nucleotide identity over 75% of their shared protein coding genes is maintained between these two pathogens, leaving much conjecture regarding the molecular determinants responsible for producing these vastly different disease etiologies, host preferences and transmission routes. One idea is that coordinated production of distinct factors required for host adaptation and virulence in response to specific environmental cues could contribute to the distinct pathogenicity distinguishing these two species. Small non-coding RNAs that direct posttranscriptional regulation have recently been identified as key molecules that may provide such timeous expression of appropriate disease enabling factors. Here the burgeoning field of small non-coding regulatory RNAs in Yersinia pathogenesis is reviewed from the viewpoint of adaptive colonization, virulence and divergent evolution of these pathogens.